PROJECT ACTIVITY AS A MECHANISM OF INNOVATION (ON THE EXAMPLE OF VINNYTSIA HIGHER VOCATIONAL SCHOOL OF SERVICES) (Innovative professional education, 2022)
Vinnytsia Higher Vocational School of Services is implementing a set of measures to improve the quality of training of future skilled workers. For this purpose, a number of European projects are being implemented aimed at the formation of life and professional competencies, further employment of graduates of the institution, the development of a strategy of «lifelong learning». The main results of international project activities are presented.
Keywords: professional education; project activity; international projects; problem-oriented education; institutions of professional (vocational) education